Editorial (2021)
The January-June 2021 edition of the journal Revista IUSTA has proposed to the academic community articles resulting from institutional research projects, whose content reveal legal novelty and complexity in the Colombian legal system. To that end, this edition offers its readers topics related to Andean Community law and Colombian land use planning; likewise, classic contents of public procurement are addressed, such as the importance of bidding documents in public works contracts. On the other hand, the edition also presents novel reflections by academics on asbestos in Colombia, on the role of legal clinics in the post-conflict and in relation to public policies in the framework of land ownership by rural women.